Alternovértice: as festas alternativas de Belém do Pará como indutor para a prática de ensino do Contato Improvisação - SILVA, Allan Patrick Lima da (2018)
This research aims to develop possibilities for teaching the foundations of the language of Contact Improvisation from analyzes observed in the field, in the mold of Feasts Alternatives of Belém do Pará. Resulting in relations arising triads of Contact Improvisation Festivals and Alternatives, enabling research a look on the relationship of the body, the environment and the other (single), to be a process of teaching and learning in the language of dance in relation to Contact Improvisation. Some elements of Feasts Alternatives were evidenced throughout this text, mode of organization, audience, media. Just like the description of a new research model of movement that was created by Steve Paxton, Contact Improvisation. In the course of writing will be noticeable to the relationships and correlations that will be interconnected by means of the characteristics that many times it is parallel its central ideas. The research concludes on a path to allow those who wish to spread the language of Contact Improvisation, assuming the understanding of bases that language develops. Because there are no records of how to apply such bases, throw me to propose new possibilities that are developed in classes / experiments / jobs.